Comparison of efficacy of low‐carbohydrate and low‐fat diet education programs in non‐alcoholic fatty liver disease: A randomized controlled study. Issue 3 (4th July 2017) - Jang, Eun Chul; Jun, Dae Won; Lee, Seung Min; Cho, Yong kyun; Ahn, Sang Bong
Abstract : Aim: Composition of macronutrients is important in non‐alcoholic fatty liver disease (NAFLD). Diet education programs that mainly emphasize reducing fat consumption have been used for NAFLD patients. We compared the efficacy of conventional low‐fat diet education with low‐carbohydrate diet education in Korean NAFLD patients. Methods: One hundred and six NAFLD patients were randomly allocated to low‐fat diet education or low‐carbohydrate education groups for 8 weeks. Liver chemistry, liver / spleen ratio, and visceral fat using abdominal tomography were measured. Results: Intrahepatic fat accumulation decreased significantly in the low‐carbohydrate group compared to low‐fat group (liver/spleen 0.85 vs. 0.92, P < 0.05). Normalization of ALT activity at week 8 was 38.5% for the low‐carbohydrate and 16.7% for the low‐fat group ( P = 0.016). Not only liver enzyme, but also low density lipoprotein cholesterol and blood pressure levels significantly decreased in the low‐carbohydrate group. Total energy intake was also further decreased in the low‐carbohydrate group compared to the low‐fat group. Although body weight changes were not different between the two groups, the carbohydrate group had a lower total abdominal fat amount. Conclusions: A low‐carbohydrate diet program is more realistic and effective in reducing total energy intake and hepatic fat content in Korean NAFLD patients. This trial is registered with the National Research Institute of Health: KCT0000970 (https://cris.nih.go.kr/cris/index.jsp ).